TINJAUAN HUKUM ISLAM TERHADAP PERILAKU ISTIMNA’ DAN IMPLIKASINYA TERHADAP KUALTIAS RUMAH TANGGA: STUDI PADA KARYAWAN PT PERTAMINA DURI - Almadjid, Juvan Pabuka (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the implications of masturbation behavior on the quality of marital relationships and household stability among employees of PT. Pertamina Duri, as well as to examine the Islamic legal perspective on this phenomenon. This research employs a qualitative approach with a descriptive method, utilizing in-depth interviews and document studies. The sample was selected purposively, consisting of married employees with experiences related to masturbation behavior. The findings reveal that the primary factors driving masturbation behavior in marriage include pre-marital habits, physical distance from one’s spouse, stress, emotional pressure, and a lack of education about reproductive health. The impact of masturbation on marital relationships varies; in some cases, excessive masturbation can reduce sexual desire towards a spouse and trigger conflicts, whereas for others, masturbation within reasonable limits does not negatively affect household harmony if supported by good communication between partners. From an Islamic legal perspective, the majority of scholars prohibit masturbation except in cases of necessity to prevent adultery. However, within the context of marriage, masturbation assisted by a spouse is more acceptable compared to self-masturbation. Islam emphasizes the importance of open communication in marriage to maintain a balance between biological needs and household harmony.